Plasma treated water – A promising electrolyte to produce nanoporous titanium dioxide nanotubes. Issue 9 (1st February 2017) - Ambujakshan, Arun T.; Sadek, Abu; Magniez, Kevin; Mateti, Srikanth; Mayes, Edwin; Devi, Gayathri; Pringle, Jennifer M.; Plessis, Johan du; Chen, Zhiqiang; Corr, Cormac S.; Hodgson, Peter D.; Dai, Xiujuan J.
Abstract : Plasma‐treated water is used as an environmentally friendly electrolyte for the synthesis of nanoporous titanium dioxide nanotubes by anodization of titanium. The possible mechanism of nanotube formation in the process is studied. The reactive species hydrogen peroxide and nitrate can be selectively produced in a gas bubble discharge in liquid using argon plasma or air plasma, respectively. It is observed that hydrogen peroxide enhances only the formation of an oxide layer, while nitrate forms pores on this oxide layer. It is proposed that the nitrate determines the formation of nanoporous nanotubes, while hydrogen peroxide enhances the oxidation. Abstract : Plasma‐treated water is used as an electrolyte to replace the toxic chemicals in anodization. Air plasma that generates NO3 − contributes to TiO2 nanotube formation, while argon plasma produced H2 O2 speeds up the reaction.